(untitled) (Research, Society and Development, 2022)
Given the increase in diagnoses of Autism Spectrum Disorder in children and adolescents worldwide, a study is necessary to understand how these diagnoses are made. Thus, the present study aimed to investigate the age at which an Autistic Spectrum Disorder (ASD) diagnosis is made in patients of a private clinic in a city in the metropolitan area of Porto Alegre, Rio Grande do Sul state, as well as which professionals were involved in this process. Nine parents participated, being 7 mothers and 2 fathers, with ages between 29 and 62 years old, all of them were in a stable union; only one of the interviewees did not have a complete high school education. This is a qualitative study, with multiple case study design. The results were organized into categories according to the age of the children at the time of diagnosis. It is important to emphasize that most of the parents interviewed had observed atypical behavior in their children before they were 3 years old, and that communication and language impairment and delay were the earliest symptoms observed by them, followed by social behavior impairment.